A liminal approach to parents in leadership positions in schools with students of high socioeconomic background in Israel. Issue 1 (26th September 2019) - Addi-Raccah, Audrey; Friedman, Noa
Abstract : Purpose: Parents' collective involvement in their children's education takes the form of holding leadership positions in schools. Employing the concept of liminality, which is used in anthropological and sociological approaches, the purpose of this paper is to explore the features of parent leadership in schools (PLS). Design/methodology/approach: Interviews were conducted with 18 individuals: 11 chairpersons and 7 members of the parent leadership of 11 primary schools in Israel attended by students of high socioeconomic backgrounds. Findings: Data analyses disclose PLS as a liminal framework, which constitutes both formal and informal dimensions, whether these be its in-school limited activities or out-of-school actions in introducing change and supporting the institutions. PLS's functions are restricted by school principals, but simultaneously enhance school principals' position. Practical implications: The study's findings carry implications for school collaboration with external entities. School principals need to support PLS and keep encouraging entrepreneurship, creativity and innovation. There is a need for acknowledging the value of PLS's contributions whereas policy makers must provide more guidelines and support to parent leaders. Originality/value: The study focuses on exploring the position of collective parental involvement in schools. This issue is of significance in a time where parents gain more responsibility over their children's education and schools support more collaborative relationships with external agencies. The study highlights the benefits of parents in leadership positions for school benefits and for school principals' legitimacy, from the approach of liminality.